Technical and Non-Technical Skills Required by TVET Teacher in Digital Learning Based on TPACK Framework; A Systematic Literature Review - Binti Abdullah, Aida Aisyah Moktar; Masek, Alias (Journal of TVET and Technology Review, 2024)
Research examining the implementation of Information and Communication Technologies (ICTs) in both general education and Technical and Vocational Education and Training (TVET) has identified several challenges faced by stakeholders in achieving successful integration such as shortage of time for preparing teaching materials and a lack of knowledge and skills in presenting advanced ICT teaching materials, lack of motivation among TVET teachers and lack of hands-on experience may hinder their ability to effectively translate theoretical concepts into real-world applications. In this regard, the purpose of this research is to identify the technical, non-technical skills required by TVET teachers in digital learning and to customize the technical and non-technical skills by following the TPACK framework. PRISMA model will be used includes the processes of identification, screening, eligibility, and inclusion. Qualitative method with thematic analysis will be used that include open, axial and selective code. There are 4 technical skill required by the TVET teacher which are Digital Tool Skill, Re-mix Digital Learning Resource, Digital Management and Pedagogic Skill while 3 non-technical skills which are Personal-ethical Skill, Communication Skill and Adaptability Skill in digital learning. There are 20 articles, journals and books which are relevant to this research. The proposed model for technical and non-technical skills based on the TPACK framework is developed for TVET teacher in higher institution learning.